Electronic structure of Pb1-xLaxTiO3 ferroelectric materials from Ti 2p and O 1s soft x-ray absorption spectroscopy - Mastelaro, V. R.; Neves, P. P.; de Lazaro, SR; Longo, Elson [UNESP]; Michalowicz, A.; Eiras, J. A. (American Institute of Physics (AIP), 2006)
The electronic structure of Pb1-xLaxTiO3 (PLT) compounds for x ranging from 0 to 30 at. % of La is investigated by means of soft x-ray absorption near edge structure (XANES) at the Ti L-3,L-2 and O K edges. The greatest modification in the structure of the Ti 2p XANES spectra of the PLT compounds is observed in the region of the high energy peak of the L-3 edge (e(g) states), which exhibits a splitting in the undoped sample. As the amount of lanthanum increases, this splitting becomes less pronounced. This modification is interpreted as a decrease in the degree of disorder of titanium atoms, which is correlated to the substitution of Pb by La atoms. The structural changes observed at the low energy peaks of the O K-edge XANES spectra of the PLT compounds may be interpreted in terms of hybridization between O 2p, Ti 3d, and Pb 6p orbitals. A decrease in the degree of hybridization observed as Pb atoms are replaced by La atoms may be related to the differences in the ferroelectric properties observed between x=0.0 and x=0.30 compounds. (c) 2006 American Institute of Physics.